ASPECTS OF THE DEVELOPMENT OF LEGAL REGULATION FOR GENETIC DIAGNOSTICS IN THE RUSSIAN FEDERATION - Sergeevich Samoylov, Alexander; Goloborodko, Evgeny; Astrelina, Tatyana; Vyacheslavovna Dedova, Elizaveta; Valentinovna Сhykovskaya Irina; Vladimirovna Gubaeva, Tatyana (Revista Inclusiones, 2020)
The need for jurisdiction in relations in the field of medicine, including genetic methods and research on humans, is determined by its very development and the emergence of the necessary legal regulation of relations regarding various aspects of the right to health and medical care and ending with the right to preserve information about human health, management, and control of this field. The development of genomic medicine is inextricably linked with two fields that are of fundamental importance for legal regulation in this area, namely gene diagnostics and gene therapy. Thus, having studied the Russian and foreign (national) legislation one can conclude that Russian legislation stands out by legal gaps and lack of unified standards.